The Fyn–ADAP Axis: Cytotoxicity Versus Cytokine Production in Killer Cells - Gerbec, Zachary J.; Thakar, Monica S.; Malarkannan, Subramaniam (Frontiers in Immunology, 2015)
Lymphocyte signaling cascades responsible for anti-tumor cytotoxicity and inflammatory cytokine production must be tightly regulated in order to control an immune response. Disruption of these cascades can cause immune suppression as seen in a tumor microenvironment, and loss of signaling integrity can lead to autoimmunity and other forms of host-tissue damage. Therefore, understanding the distinct signaling events that exclusively control specific effector functions of ‘killer’ lymphocytes (T and NK cells) is critical for understanding disease progression and formulating successful immunotherapy. Elucidation of divergent signaling pathways involved in receptor-mediated activation has provided insights into the independent regulation of cytotoxicity and cytokine production in lymphocytes. Specifically, the Fyn signaling axis represents a branch point for killer cell effector functions and provides a model for how cytotoxicity and cytokine production are differentially regulated. While the Fyn-PI(3)K pathway controls multiple functions including cytotoxicity, cell development and cytokine production, the Fyn-ADAP pathway preferentially regulates cytokine production in NK and T cells. In this review, we discuss how the structure of Fyn controls its function in lymphocytes and the role this plays in mediating two facets of lymphocyte effector function, cytotoxicity and production of inflammatory cytokines. This offers a model for using mechanistic and structural approaches to understand clinically relevant lymphocyte signaling.